2017
DOI: 10.1016/j.ram.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of honey bee ( Apis mellifera ) viruses in temperate and subtropical regions from Argentina

Abstract: In Argentina, bee virus studies are still incipient, and there are no studies regarding the climatic effect. The aim of this study was to assess and compare the presence of honeybee viruses in different climatic regions from Argentina. A total of 385 colonies distributed in five Argentinean eco-regions were examined to evaluate the percentage of infestation with Varroa destructor and the presence of seven virus species (Deformed wing virus, DWV; Acute bee paralysis virus, ABPV; Chronic bee paralysis virus, CBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
12
0
7
Order By: Relevance
“…Asymptomatic or covert infections seem to be very common in honey bees, for example, about 15% of the bees assessed in this study were infected with acute and/or chronic paralysis virus, some at relatively high concentrations; however, none of them showed visible signs of disease (impaired movements, trembling, above‐average loss of hair). This absence of disease symptoms in infected bees was noted already when the paralysis viruses were first described (Bailey, Gibbs, & Woods, ) and affirmed in many subsequent publications, for example, Gauthier et al (); Hung, Shimanuki, and Knox (); Molineri et al (); Nielsen et al (); and Tentcheva et al (). Gauthier et al () quantified viral loads in asymptomatic bees by qPCR and found high concentrations similar to and even exceeding those reported here.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Asymptomatic or covert infections seem to be very common in honey bees, for example, about 15% of the bees assessed in this study were infected with acute and/or chronic paralysis virus, some at relatively high concentrations; however, none of them showed visible signs of disease (impaired movements, trembling, above‐average loss of hair). This absence of disease symptoms in infected bees was noted already when the paralysis viruses were first described (Bailey, Gibbs, & Woods, ) and affirmed in many subsequent publications, for example, Gauthier et al (); Hung, Shimanuki, and Knox (); Molineri et al (); Nielsen et al (); and Tentcheva et al (). Gauthier et al () quantified viral loads in asymptomatic bees by qPCR and found high concentrations similar to and even exceeding those reported here.…”
Section: Discussionmentioning
confidence: 58%
“…et al (2007);Hung, Shimanuki, and Knox (1996);Molineri et al (2017);Nielsen et al (2008); andTentcheva et al (2004) Gauthier et al (2007). …”
mentioning
confidence: 99%
“…The previously developed TaqMan assays for ABPV, BQCV, CBPV, and DWV showed good performance and reliability also for the detection and quantification of a broad genetic range of previously determined Slovenian honeybee viral strains [ 4 , 14 , 28 ]. The newly developed TaqMan RT-qPCR assay for detecting and quantifying SBV from this study is a good alternative and improvement of previously described assays, in terms of SYBR Green or MGB-probes [ 30 , 42 , 43 , 44 ], while SYBR Green also provides non-specific detection, and MGB-probes are not as stable as TaqMan probes. Because of this, TaqMan probes are the most frequently used in routine diagnostic laboratories for diagnostics of infectious diseases [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…6(1).2020 ABPV was detected with high prevalence percentage (21.5%) in Argentinean apiaries. In addition to its detection, co-infections with ABPV and BQCV were reported [9]. However, despite increasing knowledge on bee viruses, the information about the presence and effect of virus in Argentinean queen rearing apiaries is lacking.…”
Section: Mod Concep Dev Agronomentioning
confidence: 99%
“…In addition, previous reports demonstrated that the virus present in different bee food sources (honey, pollen and royal jelly) may be transmitted horizontally between adult bees such as queens, workers, or drones [6]. Recent studies showed the presence of virus in honeybee colonies from Argentinean producers located along temperate and subtropical regions [7][8][9]. Notably, many honeybee viruses have been detected in Argentinian stingless bees and bumblebees [10,11].…”
Section: Introductionmentioning
confidence: 99%